A review on the effect of bioethanol dilution on the properties and performance of automotive lubricants in gasoline engines. Issue 71 (13th July 2016) - Khuong, L. S.; Zulkifli, N. W. M.; Masjuki, H. H.; Mohamad, E. Niza; Arslan, A.; Mosarof, M. H.; Azham, A.
Abstract : Owing to the growing concern over the depletion of fossil fuels and the rising rate of greenhouse gas emissions which will lead to global warming, many researchers are now dedicated to producing biofuels in order to solve the above-mentioned issues. Abstract : Owing to the growing concern over the depletion of fossil fuels and the increasing rate of greenhouse gas emissions which will lead to global warming, many researchers are now dedicated to producing alternative biofuels in order to help address the above-mentioned issues. Bioethanol is one of the biofuels which has gained much attention for use in existing gasoline engines and nowadays, bioethanol is blended with gasoline at higher proportions since the use of bioethanol helps reduce exhaust emissions such as soot, carbon oxides and unburned hydrocarbons. However, the use of bioethanol has undesirable effects on the tribological properties of the fuel blend, and it is possible that the automotive lubricant will be contaminated with diluted oxygenated bioethanol during engine operations. Moreover, the addition of bioethanol into gasoline alters the properties of the fuel, which in turn affects the vehicle performance. Since bioethanol has a significantly higher boiling point and latent heat of vaporization compared to gasoline, it is likely that the level of bioethanol dilution in the automotive lubricant will increase significantly, which in turn degrades the quality of the lubricant to protect the engine components against friction and wear. The purpose of this review paper is to highlight the physicochemical properties of bioethanol and its blends as well as the effect of bioethanol dilution on the properties and performance of automotive lubricants in gasoline engines. Based on the key findings, it can be concluded that bioethanol dilution has a significant effect on the properties of automotive lubricants, particularly on oil consumption, corrosion, wear and sludge, which will lead to engine failure. However, the contamination of automotive lubricants can be prevented by the addition of additives such as dispersants, detergents or antioxidants, which will improve the lubricity and performance of the engine oil.